The Influence of the Leading Teacher Program on the Teachers’ Pedagogical and Professional Competence - Yeni Lutfiatun Fajariani; Muthmainah Muthmainah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
The Leading Teacher Program is a program to enable teachers to manage learning independently, reflectively, collaboratively, innovatively, and in a student-centered manner. However, in reality, many teachers have not received training in creative and innovative learning management. This study aims to analyze the influence of the Leading Teacher Program on the pedagogical and professional competence of Kindergarten teachers in Sleman Regency, Yogyakarta Special Region Province. The study used a quantitative approach. The subjects of the study were 74 Kindergarten leading teachers in Sleman Regency, Yogyakarta Special Region Province. During the training, teachers were actively involved in discussions and completed assigned tasks. The instruments used to collect data were the Leading Teacher Program Questionnaire, the Pedagogical Competence Questionnaire, and the Professional Competence Questionnaire, which had previously been tested for validity and reliability. The data analysis technique used was quantitative analysis. The results of the study showed that (1) there was a positive and significant influence of the leading teacher program on teachers' pedagogical competence, with a contribution of 68.2%. (2) There was a positive and significant influence of the leading teacher program on teachers' pedagogical competence, with a contribution of 62%. The research concludes that the better the implementation of the teacher-in-charge program, the better the pedagogical and professional competencies of kindergarten teachers. Teachers are able to understand the objectives of curriculum development, creatively process learning materials, routinely reflect on their performance, and continuously learn and develop themselves in line with technological developments.